A Multimodal A∗ Algorithm to Solve the Two-Dimensional Optimization Problem of Accompanying a Person for an Intelligent Wheelchair - Kalenberg, Matthias; Lieret, Markus; Hofmann, Christian; Franke, Jörg (45th Annual International Conference of the IEEE Engineering in Medicine and Biology Conference, EMBC 2023, 2023)

Environment representation and path planning for unmanned aircraft in industrial indoor applications - Lieret, Markus; Kalenberg, Matthias; Hofmann, Christian; Franke, Jörg (FAIM 2021, 2021)
CRIS-Team WoS Importer:2022-10-28

Human Comfort Factors in People Navigation: Literature Review, Taxonomy and Framework - Kalenberg, Matthias; Hofmann, Christian; Martin, Sina; Franke, Jörg (Robotics, Computer Vision and Intelligent Systems. 4th International Conference, ROBOVIS 2024, Rome, Italy, February 25–27, 2024, Proceedings, 2024)
Due to demographic shifts and improvements in medical care, person navigation systems (PNS) for people with disabilities are becoming increasingly important. So far, PNS have received less attention than mobile robots. However, the work on mobile robots cannot always be transferred to PNS because there are important differences in navigating people. In this paper, we address these differences by providing a comprehensive literature review on human comfort factors in people navigation, presenting a unified taxonomy for PNS and proposing a framework for integrating these factors into a navigation stack. Based on the results, we extract the key differences and human comfort factors that have been addressed in current literature. Furthermore, the literature review shows that there is no unified taxonomy in this field. To address this, we introduce the term people navigation and a taxonomy to categorize existing systems. Finally, we summarize the human comfort factors that have been considered so far and provide an outlook on their implementation. Our survey serves as a foundation for a comprehensive research in people navigation and identifies open challenges.<br
Keywords: People navigation; Person navigation system; Human comfort factors

Robotics simulation – A comparison of two state-of-the-art solutions - Zwingel, Maximilian; May, Christopher; Kalenberg, Matthias; Franke, Jörg (ASIM 2022 Proceedings Langbeiträge, 2022)
Simulation plays a significant role in development and deployment of robotics systems. Depending on the planned tasks, different functionalities shift into focus. For mobile robotics systems using the Robot Operating System (ROS), Gazebo has been the goto solution for simulating behavior, sensors, and interaction with environments for many years. With the availability of numerous novel solutions, a comparison of the different strengths from a use-case perspective becomes necessary. In our paper, we compare Gazebo and NVIDIAs Isaac Sim in the context of ROS-based autonomous mobile robots. Special attention is given to the integration of the simulators in the ROS-environment and their ability in regards to sensor simulation. This paper aims to provide a comparison between different features in Gazebo and NVIDIA Isaac Sim for simulating mobile robots and sensor systems. <br